Exergames for falls prevention in sheltered homes: a feasibility study - Stanmore, Emma; Eost-Telling, Charlotte; Meekes, Wytske; Banham, Kelly; Chillala, Jay; Roy, Bibhas; Firth, Joseph (Frontiers in Public Health, 2024)
Introduction Falls prevention is a global priority given its substantial impact on older adults and cost to healthcare systems. Advances in telerehabilitation technology such as `exergaming’ show potential for delivering accessible, engaging exercise programs for older adults. This study aimed to establish the feasibility, acceptability and usability of exergaming in sheltered housing. Methods A mixed-methods study with participants randomised in 2 sheltered housing facilities to intervention (n = 1 home, 12 participants) and control (n = 1 home 2, 12 participants) provided usual care for all, (physiotherapy prescribed strength and balance exercises and falls prevention advice) and a 6-week supervised exergaming programme (MIRA) offered 3 times per week to the intervention group only. At 6 weeks, feasibility, usability and acceptability outcomes were collected and analysed using descriptive statistics; qualitative focus groups with participants and interviews with staff were also completed and thematically analysed to elicit barriers and facilitators to usability and acceptability. Results Mean exercise per week increased from 10.6 to 14.1 minutes in the control group and 9.6 to 36.8 minutes in the intervention group. All study processes and measures appeared feasible; 72% of those invited consented to taking part and 92% completed 6-week follow-up. Individual domains for the System Usability Scores (SUS) showed participants felt `very confident’ using the system with support (70%), would `like to use exergames frequently’ (50%) and found the system `easy to use’ (90%). However, they also felt they `needed to learn a lot at the beginning’ (40%) and would `need technical support’ (70%) for independent use of the exergames. Mean overall SUS was 63 reflecting moderate usability for independent use. Qualitative data indicated exergames were well received and highlighted motivational and social aspects; costs and set up. Staff also felt exergaming complemented traditional care. Discussion Our study contributes to the evidence guiding the use of exergames to deliver suitable falls prevention interventions for older adults within sheltered housing in community settings.